The Effects of Simulated Mild Leg Length Discrepancy on Gait Parameters and Trunk Acceleration - Jung, Soo-jung; An, Duk-hyun; Shin, Sun-shil (Han'guk Chŏnmun Mulli Ch'iryo Hakhoe chi = Journal of the Korean Academy of University Trained Physical Therapists, 2018)
Background: Leg length discrepancy (LLD) leads to many musculoskeletal disorders and affects daily activities such as walking. In the majority of the population, mild LLD is a common condition. Nevertheless, it is still controversy among researchers and clinicians on the effects of mild LLD during gait, and available studies have largely overlooked this issue. Objects: The purpose of the present study is to investigate the effects of mild LLD on the gait parameters and trunk acceleration. Methods: A total of 15 female and male participants with no evidence of LLD of >.5 ㎝ participated in the present study. All participants walked under the following two conditions: (1) The non-LLD condition, where the participants walked in shoes of the same heel height; (2) A mild LLD condition induced by wearing a 1.5 ㎝ higher heel on the right shoe. The GAITRite system and tri-axial accelerometer were used to measure gait parameters and trunk acceleration. To compare the variation of each variable, a paired t-test was performed. Results: Compared to the non-LLD condition, step time and swing phase were significantly increased in the mild LLD condition, while stance phase, single support phase, and double support phase significantly decreased in the short limb (p<.05). In the long limb of the mild LLD condition, single support phase significantly increased, while swing phase significantly decreased (p<.05). Furthermore, significant decrease in the gait velocity and cadence in the mild LLD condition were observed (p<.05). In the comparison between both limbs in the mild LLD condition, the step time and swing phase of the short limb significantly increased compared with the long limb, while step length, stance phase, and single support phase of the long limb significantly increased compared with the short limb (p<.05). Additionally, trunk acceleration of all directions (anterior-posterior, medial-lateral, vertical) significantly increased in the mild LLD condition (p<.05). Conclusion: The results of the present study demonstrate that mild LLD causes altered and asymmetrical gait patterns and affects the trunk, resulting in inefficient gait. Therefore, mild LLD should not be overlooked and requires adequate treatment. KCI Citation Count: 0